Hormone receptor positive, HER2 negative metastatic breast cancer: Impact of CDK4/6 inhibitors on the current treatment paradigm. (4th October 2018) - Boyle, Frances; Beith, Jane; Burslem, Katie; de Boer, Richard; Hui, Rina; Lim, Elgene; McCarthy, Nicole; Redfern, Andrew; Woodward, Natasha
Abstract: Resistance to endocrine therapy is a significant therapeutic challenge in the treatment of women with hormone receptor positive (HR+), human epidermal growth factor receptor 2 negative (HER2–) advanced breast cancer. Cyclin‐dependent kinase (CDK)4/6 inhibitors in combination with endocrine therapy have been shown to improve progression free survival, overall response rate and clinical benefit rate in women with HR+ HER2– metastatic breast cancer compared with endocrine therapy alone. This review examines the clinical evidence to support the use of CDK4/6 inhibitors in first and second line settings. Practical guidance is provided for the use of CDK4/6 inhibitors, including tolerability data, monitoring requirements and management of key toxicities for each of the available agents.